(3GdfXGe GdbGfhfj dTgGOGJ GdGjOGY GdhWfjI hGdOhdjI(B:s (3OQGSI ebGQfI(B/s - (3EjeGf UHQi eMehO GdOShbi,s; (3Ndjd ajcJhQ JGOQSs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3JYO TgGOGJ GdEjOGY GdOhdjI (B- (3ef Cge GdJWhQGJ GdeGdjI GdMOjKI GdJi XgQJ ai GdBhfI GdGNjQI ai CShGb GdeGd GdOhdjI hGdeMdjI MjK CJGMJ ddTQcGJ GdeMdjI GdJYGed ai CShGb GdeGd GdOhdjI hJhSjY bGYO GdeSGgejf GdeJYGedjf Ydi CSgegG hJMbjb GdEfJTGQ GdOhdi hJfejI QCS eGdgG(B. (3hESJgddfG GdOQGSI HaUd JegjOi Yf GdCOhGJ GdeGdjI GdMOjKI hGdJejjR HjfgG hHjf TgGOGJ GdEjOGY GdOhdjI, hHOCfG HMKfG HGdHGH GdChd (B: (3HGdCMcGe GdYGeI dTgGOGJ GdEjOGY GdOhdjI , CeG GdHGH GdKGfi (B: (3abO JfGhdfG ajg TQhW EUOGQ hJOGhd TgGOGJ GdEjOGY GdhWfjI hGdOhdjI(B. (3hJgOa GdOQGSI Edi HjGf WHjYI GdBKGQ GdEbJUGOjI hGdeGdjI GdJi JMOKgG TgGOGJ GdEjOGY ai eUQ hOhd GdYGde GdeNJdaI Ydi ENJdGa GdbhGfjjf GdeMOOI hGdefXeI dgG hHjGf YeG GPG cGf dgG LhGfH CNQi EjLGHjI cGajI hJCKjQGJgG GdVGQI Ydi GdEbJUGO ai eUQ hGdHdOGf GdCNQi(B. (3ceG JhUdfG ai fgGjI GdHMK dHYV GdfJGFL efgG Cf TgGOGJ GdEjOGY GdOhdjI CUHMJ COGI HOjdI ai CShGb GdeGd GdOhdjI dRjGOI MLe GdCSJKeGQGJ hQDhS GdCehGd GdYGdejI Yf WQjb JYGed GdTQcGJ GdeMdjI ai GdHhQUGJ GdYGdejI HehLHgG(B. (3ceG fhUi ai fgGjI GdHMK HCf CShGb GdChQGb GdeGdjI aj CeqS GdMGLI GdBf CcKQ ef Cj hbJ eVi Edi bGfhf eMce ddEaUGM hGdTaGajI jYGdL ChLg bUhQ GdfXe GdMGdjI ddHhQUGJ(B.s
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI(B- (3cdjI GdMbhb(B- (3bSe GdbGfhf GdJLGQj, (B2022s
(3HHdjhLQGajG(B: (3U(B. 266-284.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdGOhGJ GdeGdjI GdMOjKIs; (3GdYbhO GdeSJbHdjIs; (3TgGOGJ GdGjOGYs; (3TgGOGJ GdcQHhfs; (3TgGOI GdGjOGY GdGeQjcjIs; (3JQNjV TQcGJ GdSeSQIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs